Thermopower of a Luttinger-liquid-based two-channel charge Kondo circuit: nonperturbative solution - Parafilo, Anton V.; Nguyen, Thanh Thi Kim (Communications in Physics, 2023)
Recently, the influence of electron-electron interactions on the thermoelectric transport in a two-channel charge Kondo circuit has been studied in [Phys. Rev. B 105, L121405 (2022)]. In this paper, we revisit the Luttinger-liquid-based model and discuss in details the limit where the spin field is noninteracting (\(g_σ = 1\)) and the interaction in the charge sector is repulsive (\(0< g_ρ ≤ 1\)). The thermoelectric transport coefficients are computed nonperturbatively with respect to the reflection amplitude at the quantum point contact. At low temperatures the thermopower shows the non-Fermi liquid behavior in the vicinity of the Coulomb peaks. We also demonstrate that repulsive interaction results in the enhancement of the thermoelectrical power.